2022
DOI: 10.1002/eap.2745
|View full text |Cite
|
Sign up to set email alerts
|

Are we telling the same story? Comparing inferences made from camera trap and telemetry data for wildlife monitoring

Abstract: Estimating habitat and spatial associations for wildlife is common across ecological studies and it is well known that individual traits can drive population dynamics and vice versa. Thus, it is commonly assumed that individual‐ and population‐level data should represent the same underlying processes, but few studies have directly compared contemporaneous data representing these different perspectives. We evaluated the circumstances under which data collected from Lagrangian (individual‐level) and Eulerian (po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Individual behaviour scales up to population‐level distributions (Mueller & Fagan, 2008 ), so results from the two perspectives can, in principle, be reconciled. In practice, few studies have compared the Eulerian and Lagrangian approaches to studying population‐level space use (but see Phillips et al, 2019 ; Bassing et al, 2022 ). In our case, we find both similarities and discrepancies between our work (Eulerian) and previous studies (Lagrangian) of elk habitat selection in northern Yellowstone (Appendix S7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individual behaviour scales up to population‐level distributions (Mueller & Fagan, 2008 ), so results from the two perspectives can, in principle, be reconciled. In practice, few studies have compared the Eulerian and Lagrangian approaches to studying population‐level space use (but see Phillips et al, 2019 ; Bassing et al, 2022 ). In our case, we find both similarities and discrepancies between our work (Eulerian) and previous studies (Lagrangian) of elk habitat selection in northern Yellowstone (Appendix S7 ).…”
Section: Discussionmentioning
confidence: 99%
“…White‐tailed deer fawns were fitted with expandable, very high frequency (VHF) radio collars at capture (Model M4210, Advanced Telemetry Systems, Isanti, MN, USA and Model Vertex Natal‐linked, Vectronic Aerospace, Berlin, Germany). We captured neonatal elk opportunistically and by targeting VIT expulsions from collared adult female elk (Bassing et al 2022). Adult elk were not included in our study as none were confirmed to die by predation.…”
Section: Methodsmentioning
confidence: 99%
“…Further studies should also consider other ways of validating expert models. Other potential sources of validation data could come from GPS or other tracking devices that might show direct relationships with animal habitat selection (Bassing et al., 2023). We recommend validating expert models either with camera surveys explicitly designed to sample across a range of predicted values or with movement data from animal tracking.…”
Section: Discussionmentioning
confidence: 99%